2020
DOI: 10.3390/ijms21020570
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals for the Prevention and Treatment of Gastric Cancer: Effects and Mechanisms

Abstract: Gastric cancer is the fifth most common cancer, and the third most prevalent cause of cancer-related deaths in the world. Voluminous evidence has demonstrated that phytochemicals play a critical role in the prevention and management of gastric cancer. Most epidemiological investigations indicate that the increased intake of phytochemicals could reduce the risk of gastric cancer. Experimental studies have elucidated the mechanisms of action, including inhibiting cancer cell proliferation, inducing apoptosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 133 publications
(146 reference statements)
0
48
0
Order By: Relevance
“…Fruits and vegetables contain many different phytochemicals [ 1 , 2 ]. Many studies have reported the higher intake of fruits and vegetables can reduce the risk of developing chronic disease [ 3 , 4 ]. Berries contain many bioactive compounds and are reported to have high antioxidant [ 5 ], antitumor [ 6 , 7 ] and anti-inflammatory activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fruits and vegetables contain many different phytochemicals [ 1 , 2 ]. Many studies have reported the higher intake of fruits and vegetables can reduce the risk of developing chronic disease [ 3 , 4 ]. Berries contain many bioactive compounds and are reported to have high antioxidant [ 5 ], antitumor [ 6 , 7 ] and anti-inflammatory activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, dose-dependent antioxidant and anti-proliferative effects were observed, in accordance with previous studies with other natural compounds. As already reported [ 41 , 42 , 43 ] the consumption of citrus juice and their phytochemicals plays an important role in the prevention and treatment of various cancers, including colon cancer. Moreover, their greater or lesser effect related to the tumor staging should not surprise [ 41 ].…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Mao et al [ 57 ] screened epidemiological studies and demonstrated that increased intake of phytochemicals in fruits and vegetables could reduce the risk of gastric cancer. They suggested that phytochemicals have the potential for the prevention and management of gastric cancer in humans.…”
Section: Discussionmentioning
confidence: 99%